Effect of alkali pretreatment on the structural properties and enzymatic hydrolysis of corn cob - Sahare, Padmavati; Singh, Rajkumar; Laxman, Ryali Seeta; Rao, Mala (Applied Biochemistry and Biotechnology, 2012)
An effective alkali pretreatment which affects the structural properties of cellulose (corn cob) has been studied. The pretreatment of corn cob was carried out with different combinations of alkali at varying temperatures. The most effective pretreatment of corn cob was achieved with 1 % alkali at 50 A degrees C in 4 h. The crystallinity index (CrI) and specific surface area (SSA) of untreated corn cob was 39 % and 0.52 m(2)/g wherein after alkali pretreatment CrI decreased to 15 % and SSA increased to 3.32 m(2)/g. The fungal organism was identified as Penicillium pinophilum on the basis of ITS sequence. At 5 % substrate concentration using a complete cellulase from Penicillium pinophilum the hydrolysis of untreated corn cob with 5, 10 and 20 FPU/g enzyme loadings were 11 %, 13 % and 16 %, whereas after alkali treatment the hydrolysis increased to 78 %, 90 % and 100 %, respectively. Further hydrolytic potential of commercial cellulases viz. Accellerase (TM) 1,000, Palkofeel-30 and Palkocel-40 were investigated under similar conditions.
Keywords: Corn cob; Crystallinity index; Enzymatic hydrolysis; Penicillium pinophilum; Specific surface area